2022
DOI: 10.1039/d1py01252e
|View full text |Cite|
|
Sign up to set email alerts
|

End-functionalized polymers by controlled/living radical polymerizations: synthesis and applications

Abstract: The precise design of polymers with well-defined end functionality has received great interest for synthesizing polymeric materials with advanced or distinctive properties. In the past decades, considerable attention has been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 585 publications
0
17
0
Order By: Relevance
“…Therefore, the copolymer was subjected to terminal group removal by the reaction with an excess of the thermal radical generator, that is AIBN. 76–79 The extent of the modification reaction was traced through UV/vis absorption spectroscopy (Fig. S19†), 80,81 and the typical degree of removal was higher than 0.98 without any significant side reactions such as chain coupling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the copolymer was subjected to terminal group removal by the reaction with an excess of the thermal radical generator, that is AIBN. 76–79 The extent of the modification reaction was traced through UV/vis absorption spectroscopy (Fig. S19†), 80,81 and the typical degree of removal was higher than 0.98 without any significant side reactions such as chain coupling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…And this study offers a novel material strategy for tailoring the high-temperature capacitive performance of dielectric polymers. Chenyi ( Zhou D. et al, 2022 ) have developed a series of novel polymer dielectrics, poly (arylene ether amide)s, with a giant high temperature energy storage density by designing the molecular structure. The results demonstrated that the polymer dielectrics with relatively great high-temperature capacitive properties exhibit a curly-packed structure at the molecular level.…”
Section: Construction Of All-organic Polymeric Dielectric Composites ...mentioning
confidence: 99%
“…Polymers with various topologies, such as block, graft, gradient, star, brush, dendrimer and hyperbranched polymers could be synthesized by CRP technology. In addition, CRP is also a commonly used method to modify materials in order to adjust their chemical and physical properties ( Figure 2 ) ( Bagheri et al, 2021 ; Corrigan et al, 2021 ; Gong et al, 2021 ; Zhou et al, 2021 ; Antonopoulou et al, 2022 ; Zhang et al, 2022b ; Li et al, 2022b ; Zhou et al, 2022c ; Corbin and Miyake, 2022 ; Dworakowska et al, 2022 ). ROMP is a relatively new research field in the preparation of polymer materials, which has all the characteristics of olefin metathesis reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Today, scientists can construct macromolecules of high complexity, with one possible technique being to endow conventional polymers with new functions suitable for a targeted application [ 2 ]. In this context, end-group functionalization of usual polymers [ 3 , 4 , 5 ], which evolved with the emergence and diversification of controlled polymerization methods tolerant to functional groups [ 6 ], allows for manipulation of the specific functionality of the end groups of the chains.…”
Section: Introductionmentioning
confidence: 99%